2021
DOI: 10.17221/96/2021-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Methods for monetary valuation of ecosystem services: A scoping review

Abstract: Adequate assessment of ecosystem services is important for the development of policies and management plans related to forestry activities and the environment. Carefully identified ecosystem values can determine which options policy makers should prioritize to provide the greatest benefit. There are numerous methods used by researchers to evaluate ecosystem services. The most widely applied methods are monetary valuation methods, they are often deemed to be the most pragmatic language when it comes to communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…It is widely believed that ecosystem services (ES) play a significant role in human well-being (Chopra et al 2022). Careful identification of ecosystem values can help policymakers determine what options should be prioritized to maximize benefits (Selivanov and Hlaváčková 2021). A study in China (Zhang et al 2010) revealed that ecosystems have great economic value, which humans have often overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely believed that ecosystem services (ES) play a significant role in human well-being (Chopra et al 2022). Careful identification of ecosystem values can help policymakers determine what options should be prioritized to maximize benefits (Selivanov and Hlaváčková 2021). A study in China (Zhang et al 2010) revealed that ecosystems have great economic value, which humans have often overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, people have cognitive biases that are not anomalies but common to human reasoning and judgmental processes. Because of these ndings, the method in the current form seems not to be a good indicator of well-being (Leimona et al, 2015;Selivanov & Hlaváčková, 2021). The two and probably most commonly used revealed-preference methods of ecosystem valuation are the travel-cost and hedonic pricing methods.…”
Section: Indirect Market Valuation/ Revealed Preference Methodsmentioning
confidence: 99%
“…The method allows estimating values related to the quality of the environment and tourist attractions (admiring the views, trekking, recreation, etc.) (Selivanov & Hlaváčková, 2021;Nandagiri, 2015). The method is the more conventional empirical technique used by economists to estimate economic values based on market prices and it is based on the actual behavior of what people do rather than a stated willingness to pay what people say.…”
Section: Travel Cost Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowing the value of ESS is recognized as an essential pathway to sustainability (Abson et al, 2014). Per se, a suitable assessment is needed to improve policy and decision-making linked to management of the territory (Ling et al, 2018;Dang et al, 2021;Selivanov and Hlaváčková, 2021). Thus, such assessments can provide evidence about the costs and benefits of promoting conservation and human well-being at the same time (de Groot et al, 2010).…”
Section: Introductionmentioning
confidence: 99%